Implementation Of Regional Financial Management Information System (SIPKD) In Enhancing Local Financial Accountability In Tapanuli Selatan District - Henny Wahyuni Nasution; Syafaruddin Ritonga; Nina Siti Salmaniah (International Journal of Integrated Science and Technology, 2024)
This research is titled "Implementation of the Local Financial Management Information System (SIPKD) in Improving Financial Accountability of the South Tapanuli District." The research was conducted using questionnaires (primary data) and involved several observations and interviews with relevant stakeholders. This research is of a Qualitative Descriptive nature and employs a juridical and sociological approach. Informants were selected using a combination of snowball sampling and purposive sampling. The primary data source for this study was information gathered through direct observation at the research location and interviews. The research findings indicate that the implementation of the accounting system at the Department of Community Empowerment and Villages in the South Tapanuli District utilizes the computerized SIMDA system and complies with established guidelines. All implementation stages were executed successfully. Similarly, the completeness of financial report items adheres to the regulations of SKPD Financial Reports, including Budget Realization Reports, Balance Sheets, and Notes to the Financial Statements. Transaction recording and classification are based on bookkeeping evidence, which is subsequently documented in the journal.